Právní úprava DPH v České republice a ve vybraném státě Evropské unie - Janovová, Martina (2006)
Czech Republic being new member of EU had to adjust its own national tax system to conform to principles set up by European Community law regulation. One of the areas impacted by this change is value added tax regime. Consecutive raise of indirect taxes together with appropriate direct tax rates declination are well konwn sign of EU tax policy.